Elaboración de un proyecto de la conformación de banda musical estudiantil en el Colegio Fiscal Mixto Simón Bolívar, del cantón Machala, provincia de El Oro. - Rivera Cabrera, Rafael Marcelo (2011)
Within the context of this research work where fundamental aspect is the performance of a student band. Discuss the following issues in the first chapter will inform the why and the formation of this band citing problematisation, the objectives, and assumptions.